Slipped Capital Femoral Epiphysis, Food Deserts, Poverty, and Urban/Rural Residence: Is There a Link?. Issue 3 (28th March 2023) - Luster, Taylor; Gunderson, Zachary J.; Sun, Seungyup; Loder, Randall T.
Abstract : Background: Childhood obesity is increased in food deserts, a community with little to no access to healthy food. As obesity is associated with slipped capital femoral epiphysis (SCFE), it was the purpose of this study to analyze the prevalence of SCFE patients by food desert location and its interaction with rural/urban location. Methods: A retrospective review of all consecutive patients with idiopathic SCFE treated at our institution over 11 years was performed. From the patient's address, the US Census Bureau tract in which the patient resided was determined. Using the census tract code, it was ascertained if the patient lived in a food desert and urban or rural location. Standard statistical analyses were performed; a P <0.05 was considered statistically significant. Results: There were 177 SCFE patients: 79 girls, 98 boys, 106, White, and 69 nonWhite. The average age at diagnosis was 12.1±1.7 years, the average symptom duration 4.1±5.1 months, and the average weight percentile 94±10. Of these 177 patients, 26.5% lived in a food desert, which was higher than the expected 17.5% ( P =0.023). Those living in a food desert were more commonly nonWhite (60% vs. 32%, P =0.0014). There were 25% from rural areas and 75% from urban areas. No rural SCFE patients lived in food deserts whereas 34% of urban patients lived in food deserts. The average poverty rate of the SCFE patient census tracts was 19%, no greater than the expected 15% ( P =0.32). SCFE patients living in rural census tracts had a lower poverty rate ( P <10 -6 ). Conclusions: There is a correlation with the prevalence of SCFE patients by residence in a "food desert", but not with rural/urban locale or poverty status in Indiana. Further research will be needed to see if these findings apply to other states within the United States and other parts of the world. Level of Evidence: III.